Inhibition of Gastric Acid Secretion by Unfractionated and Low Molecular Weight Heparins in the Rat - Omar M.E. Abdel Salam; Ayman R. Baiuomy; Amany Ameen (The Scientific World Journal)
The majority of patients receiving heparin preparations are at stress, which is a risk factor for the development of gastric erosions. Our aim was to examine the effect of unfractionated heparin (UFH) and low molecular weight heparins (LMWHs) on gastric acid secretion. Gastric acid secretion was induced in urethane-anesthetized rats by distention of the stomach (2 ml saline for 2 h) in addition to histamine or bethanechol stimulation. Distension-stimulated acid secretion (2 ml for 2 h) was significantly inhibited by intraperitoneal administration of UFH (2000 IU/kg, 19% reduction), enoxaparin (180 or 360 IU/kg, 59.2 and 87.1%, reduction, respectively), nadroparin (1000 or 2000 IU/kg, 36 and 60.7% reduction, respectively), and tinzaparin (3000 IU/kg, 41.3% reduction). All tested heparins also suppressed acid secretion in response to distention and histamine or bethanechol stimulation. Pretreatment with indomethacin did not abolish the gastric inhibitory action of nadroparin. After truncal vagotomy or atropine, nadroparin failed to inhibit acid secretion stimulated by histamine. Ganglionic blockade with guanethidine abolished the gastric inhibitory action of nadroparin or UFH. It is concluded that both UFH and LMWHs administered peripherally inhibit stimulated gastric acid secretion in the rat. This effect of heparins is determined by cholinergic and partly by adrenergic mechanisms.